Modeling of delamination in multilayer metals produced by explosive welding under plastic deformation - Smirnov, Sergey Vitalievich; Veretennikova, Irina Andreevna; Vichuzhanin, Dmitriy Ivanovich (Computational Continuum Mechanics, 2014)
Weed damage is one of the typical forms of material damage under deformation. The paper proposes a phenomenological model to predict damage and fracture caused by delamination in multilayer metals produced by explosive welding under plastic deformation. The intermediate layer including a weld joint accomplished in a variety of different metals and boundary zones is the object of our study. It is assumed that the material preserves macroscopic continuity up to the initiation of a lamination crack. Delamination is considered as a process of initiation and development of continuity microdefects which result in interlaminar crack formation. Delaminations form due to some combination of two basic (opening and shear) modes under plastic deformation. The model takes into account the effect of the stress state on ultimate strains causing opening - and shear - modes delaminations, damage accumulation and intermediate layer fracture for multilayer metals. Application of the model is based on the usage of peak plasticity diagrams for opening and shear modes of the intermediate layer. An experimental technique for constructing plasticity diagrams is proposed. Using of this technique, peak plasticity diagrams for opening shear modes of the bimetal intermediate layer of “steel X10 Cr Ni Ti 189 -steel C 10” were plotted. The efficiency of the model for computational experiments is verified during rolling the bimetallic strip of “steel X10 Cr Ni Ti 189 - steel C 10”. A comparison of the calculated and experimental results shows high coincidence, which is indicative of the fact that the proposed fracture model can be used in real manufacturing processes.
Keywords: damage; fracture; phenomenological model; multilayer metals; delamination; peak plasticity charts; plastic deformation; modelling; rolling